2022
DOI: 10.1097/mou.0000000000001047
|View full text |Cite
|
Sign up to set email alerts
|

Counseling for the man with severe male infertility

Abstract: Purpose of reviewThis review summarize the proper counseling for men with severe male factor infertility.Recent findingsMen who are experiencing infertility should have a semen analysis, the results of which may imply additional investigations, including genetic and hormonal. Moreover, possible modifiable factors that may harm men's reproductive health should be carefully evaluated. Finally, different treatment options are available.SummaryApproximately 15% of couples struggle with infertility. Complete evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This holistic concept encompassing both affective and cognitive dimensions conveys the need for a departure from the mechanistic paradigm in contemporary medicine, in favor of integrating a humanistic element into healthcare practices [ 64 , 65 ]. Accordingly, the inclusion of psychosocial aspects alongside biomedical measures in addressing fertility issues has emerged as a pivotal factor in achieving favorable outcomes, as perceived by both clinicians and patients [ 66 ]. Score distributions across conceptual areas of the health-related QoL captured by the SF-36 questionnaire in our study exhibited a similar pattern to the findings reported for male partners in large cohorts of Italian [ 67 ] and Iranian [ 68 ] infertile couples undergoing in vitro fertilization treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This holistic concept encompassing both affective and cognitive dimensions conveys the need for a departure from the mechanistic paradigm in contemporary medicine, in favor of integrating a humanistic element into healthcare practices [ 64 , 65 ]. Accordingly, the inclusion of psychosocial aspects alongside biomedical measures in addressing fertility issues has emerged as a pivotal factor in achieving favorable outcomes, as perceived by both clinicians and patients [ 66 ]. Score distributions across conceptual areas of the health-related QoL captured by the SF-36 questionnaire in our study exhibited a similar pattern to the findings reported for male partners in large cohorts of Italian [ 67 ] and Iranian [ 68 ] infertile couples undergoing in vitro fertilization treatment.…”
Section: Discussionmentioning
confidence: 99%